THE EFFECTIVENESS OF PICTOWORD GAME ON STUDENTS’ VOCABULARY MASTERY FOR EIGHTH GRADE IN SMP WAHID HASYIM MALANG - Afifah Rosiana (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: Learning English is a fundamental lesson for every level. English has four skills: speaking, writing, reading, listening, and three components: grammar, vocabulary, and pronunciation. Vocabulary is critical in every aspect, especially in learning English. Vocabulary is essential to learn in the process, so there were usually faced problems, especially by eighth grade students in SMP Wahid Hasyim Malang. Therefore, every student must master vocabulary to be able to communicate. The author of this study used an ex post facto research design. The hypothesis test in this study used the One Sample t-test in SPPS version 26. The formulation of the problem in this study was whether there was the effectiveness of using the Pictoword game learning method on the vocabulary mastery of students in SMP Wahid Hasyim Malang. The author used a sample of 40 students of eighth grade students in SMP Wahid Hasyim Malang. This research instrument used a posttest adapted from the learning syllabus of the revised 2013 curriculum. Based on the one sample t-test analysis, the results showed the t-count value (-10.809) < t-table (1.685), which means the alternative hypothesis was rejected. The author concluded that there was no effectiveness of using the Pictoword game method on the vocabulary mastery of eighth grade students in SMP Wahid Hasyim. This study investigates the effectiveness of using a Pictoword game on students' vocabulary mastery for eighth grade in SMP Wahid Hasyim Malang. The results of the hypothesis test indicate that the use of the game learning method using the Pictoword game has not provided effectiveness in the vocabulary mastery of the eighth grade students of SMP Wahid Hasyim Malang. Students are advised to use varied and creative supporting media as an exercise tool to improve vocabulary mastery.Keywords:Â Effectiveness, Ex Post Facto, Learning Method, Pictoword, Vocabulary Mastery.